An XML-centred approach to creating object-oriented supply chain simulation models. (6th March 2007) - Chatfield, Dean C.; Harrison, Terry P.; Hayya, Jack C.
We propose an eXtensible Markup Language (XML)-centred approach to object-oriented simulation modelling of supply chains. Our approach is fundamentally different from previous work in that it uses XML to describe the supply chain itself, as opposed to using XML to store the simulation model. We define a system that includes an XML-based markup language and a 'simulator' that contains a library of fundamental supply chain simulation classes and a simulation 'model mapper'. The simulator processes the supply chain description document and generates an object-oriented simulation model using the class library. We detail working reference implementations of the markup language (Supply Chain Modelling Language (SCML)) and the simulator (Simulator for Integrated Supply Chain Operations (SISCO)).